Elucidating the biosynthesis of the aphid sex pheromone - Partridge, Suzanne J. (2018)
The female-produced sex pheromone for many aphid species comprises a mixture of the iridoids (4aS,7S,7aR)-nepetalactone (I) and (1R,4aS,7S,7aR)-nepetalactol (II). Plant-derived biosynthesis of I and II, in plant species such as Nepeta spp. (Lamiaceae) and Catharanthus spp. (Apocynaceae), respectively, has received considerable attention due to their role as precursors to many pharmacologically active compounds, including the indole alkaloids. To test the hypothesis that aphids biosynthesize I and II de novo similarly to that elucidated for plants, isotopic labelling techniques have been deployed with oviparous pea aphids, Acyrthosiphon pisum (Homoptera: Aphididae).